Antiprotozoal activity of bicycles featuring a dimethylamino group at their bridgehead. Issue 16 (15th August 2016) - Faist, Johanna; Seebacher, Werner; Saf, Robert; Brun, Reto; Kaiser, Marcel; Weis, Robert
Graphical abstract: Abstract: Several dimethylamino-derivatives of the new compound-class 3-azabicyclo[3.2.2]nonanes were prepared. For better comparison of activity also a few analogues of bicyclo[2.2.2]octanes and 2-azabicyclo[3.2.2]nonanes were synthesized. Their activities were examined in vitro against the multiresistant K1 strain of Plasmodium falciparum and against Trypanosoma brucei rhodesiense (STIB 900). A couple of the newly synthesized compounds showed promising antiprotozoal activity and selectivity. The results of the biological tests of the novel compounds were compared with the activities of already synthesized compounds and of drugs in use. Structure–activity relationships were discussed.